Evaluation of the effects of the recommended oral dose of diflubenzuron on bovine sperm and oocyte quality using CASA and OPU-IVEP - Xavier, Marcelo Cunha; Martins, Leticia Prates; Moura, Rodrigo Martins; Morais, Divino Fabio; Barbosa, Joao Vitor Lima; Figueiredo, Ricardo Alamino; Peixer, Mauricio Antonio Silva; Andrade, Rosangela Vieira de; Viana, Joao Henrique Moreira (Frontiers in Veterinary Science, 2023)
The aim of this study was to evaluate potential effects of diflubenzuron on the production and quality of gametes, and on in vitro embryo production (IVEP) outcomes, in cattle. Two experiments were performed, the first to evaluate effects on semen, and the second on cumulus-oocyte complexes (COC) and on IVEP. Nelore (Bos taurus indicus) bulls (n=14) or heifers (n=16) were allocated into control (CG) or treatment (DIF) groups. All groups received a mineral mix supplement added (DIF) or not (CG) with diflubenzuron (30 mg/head/day), during eight weeks. Animals were weighed and blood samples were collected throughout the experimental period. Every other week, bulls were subjected to semen collection and heifers to transvaginal ultrasound-guided follicle aspiration sessions. Semen underwent physical and morphological evaluation, and samples were stored for further computer-assisted sperm analysis. The COC recovered were evaluated according to morphology and those classified as viable were sent to an IVEP laboratory. Diflubenzuron had no effect (P>0.05) on average body weight or in any blood hematological or biochemical endpoints, regardless of gender. In experiment 1, there was no difference (P>0.05) between DIF and CG groups for sperm concentration, morphology, or kinetics. In experiment 2, there was also no effect of diflubenzuron on the number of total, viable, or grade I oocytes, as well as on cleavage or blastocyst rates (P>0.05). In summary, the oral administration of diflubenzuron, within the recommended dose, has no short-term negative effects on sperm production and quality or on oocyte yield and developmental potential in vitro, in cattle.